Dopaminergic symptoms in migraine: A cross-sectional study on 1148 consecutive headache center-based patients. (October 2020) - Barbanti, Piero; Aurilia, Cinzia; Egeo, Gabriella; Fofi, Luisa; Guadagni, Fiorella; Ferroni, Patrizia
Background: Dopaminergic symptoms may be extremely pronounced in some migraine patients during the attack, representing a major source of disability. Objectives: We aimed to carefully characterize the clinical picture of migraine patients with dopaminergic symptoms in a large patients' population as a putative migraine endophenotype, allowing more precise disease management, treatment and outcome prediction. Methods: We screened 1148 consecutive tertiary care episodic and chronic migraine patients with face-to-face interviews collecting thorough data on lifestyle, socio-demographic factors, and clinical migraine features. Results: We identified 374 patients with migraine with dopaminergic symptoms (32.6%). The most frequent dopaminergic symptom was yawning followed by somnolence, nausea, vomiting, fatigue, mood changes and diuresis. Migraine patients with dopaminergic symptoms had longer attack duration (OR: 1.82; 95% CI: 1.41–2.36, p  < 0.0001), more frequent osmophobia (OR: 2.01; 95% CI: 1.50–2.69, p  < 0.0001), allodynia (OR: 1.43; 95% CI: 1.10–1.85, p  = 0.0071) and unilateral cranial autonomic symptoms (OR: 1.31; 95% CI: 1.01–1.68, p  = 0.045), but used less preventative treatments (OR: 0.74; 95% CI: 0.57–0.98, p  = 0.033) than patients without dopaminergic symptoms. Conclusions: Migraine patients with dopaminergic symptoms are characterized by a full-blown, more disabling migraine. Dopaminergic system modulation should be carefully considered in individuals with migraine with dopaminergic symptoms for both acute and preventative treatments in future ad hoc designed studies.